Working Group Session LAC 2006 of the Global Judges Forum : Summary Report - World Bank (Washington, DC, 2013)
Over fifty participants from 31 different Latin American, Caribbean, North American and European countries came together in the Buenos Aires Stock Exchange Building in order to discuss the following topics: Mediation and Arbitration in Commercial/Insolvency Cases, Streamlining Commercial Proceedings using Non-Judicial Entities and Processes, Delegation/Substitution in Enforcement Proceedings, and Judicial Cooperation and Court-to-Court-Communication in Cross-Border Insolvency Proceedings. The first three topics formed a unit as they all dealt explicitly with delegation of judicial work to non-judicial entities. The first topic dealt with possible alternative entities, such as mediators and arbitrators while the following two topics investigate which aspects of court and enforcement procedures respectively could be subjected to such delegation and substitution. The fourth topic, in contrast, touched on a completely different subject, the co-operation between courts, which, as a consequence of globalization, is of growing importance for the judiciary in the context of international insolvency law.